MENSTRUAL CYCLE AS AN OBSTACLE TO ACHIEVING MAXIMAL SPORT RESULT - Milan P. Mladenović; Vedrana V. Karan; Aleksandar V. Klasnja; Jelena Z. Popadic Gacesa; Otto F. Barak; Olivera R. Markovic; Olivera R. Markovic (Exercise and Quality of Life)
Each woman has different characteristics of menstrual cycle. The main problem is thedetermination of period in which the measuring would be carried out, so that the results could bedirectly linked to a certain hormone or phase of the menstrual cycle. Generally it could be saidthat menstrual cycle does not influence muscle contractility and maximum oxygen consumption,lactate level, heart rate, breathing volume, hemoglobin levels. Therefore, women who compete inanaerobic and aerobic sports do not have to adjust competition schedules to their menstrual cycle.On the other hand the increase of body temperature in the luteal phase of the menstrual cycle,possible cardiovascular strain in this phase, influence of progesterone on the respiratory center,the rise of breathing frequency and volume can have negative influence on long-term intensivesport activities. For this sort of activity female athletes are recommended to adjust theircompetition schedule to menstrual cycle.